Identidade étnica e territorialidade: a luta pela titulação definitiva do território quilombola de Camaputiua – Cajari – MA - Santos, Dorival dos (2015)
This survey was conducted in quilombola territory of Camaputiua, composed of 26 communities, it is located in the municipality of Cajari-MA, in an ecological region known as Baixada Maranhense. This research aimed to analyze the organizational forms that are constructed by social agents in that territory, which act as mobilization drives. Therefore, I dedicated myself to fieldwork period that occurred from the year 2008, considering that my analysis was based on observations that refer to the time frame of 2008 to 2015. To this end, we conducted open interviews, followed meetings in addition to several stays on the field where I was in the communities that make up the territory Camaputiua. From the field data, sought to reflect on the role of local social workers considering their traditional practices and knowledge of the right tools. Analyze too, from local narratives, forms of control of the mythical elements of the natural resources. These mythical beings, maintains a relationship of complicity with the families of the communities, as both are interdependent, live in form of protection to each other, by maintaining and controlling the use of natural resources. The conflicts that originated from the extensive cultivation of buffalo project, were disastrous for traditional communities living in Maranhão Lowlands, since they caused damage to the natural environment. The consequences of this project were the drastic expansion of land grabbing process, privatization of natural fields and upland forests, by building the pens great. From the development of the buffalo culture in Camaputiua territory gave up the most intense violence against the Maroons, such as imprisonment, assault threats, expulsion of residents addition to the lawsuits that put the Maroons on condition invaders. I noticed that their struggle is getting more intense maroon day. According to the narratives the definitive titling of the territory is essential for the resolution of conflicts and the permanence of the social agents on their land.